Aspartate‐Based CXCR4 Chemokine Receptor Binding of Cross‐Bridged Tetraazamacrocyclic Copper(II) and Zinc(II) Complexes. Issue 36 (26th July 2016) - Maples, Randall D.; Cain, Amy N.; Burke, Benjamin P.; Silversides, Jon D.; Mewis, Ryan E.; D'huys, Thomas; Schols, Dominique; Linder, Douglas P.; Archibald, Stephen J.; Hubin, Timothy J.
Abstract: The CXCR4 chemokine receptor is implicated in a number of diseases including HIV infection and cancer development and metastasis. Previous studies have demonstrated that configurationally restricted bis‐tetraazamacrocyclic metal complexes are high‐affinity CXCR4 antagonists. Here, we present the synthesis of Cu 2+ and Zn 2+ acetate complexes of six cross‐bridged tetraazamacrocycles to mimic their coordination interaction with the aspartate side chains known to bind them to CXCR4. X‐ray crystal structures for three new Cu 2+ acetate complexes and two new Zn 2+ acetate complexes demonstrate metal‐ion‐dependent differences in the mode of binding the acetate ligand concomitantly with the requisite cis ‐V‐configured cross‐bridged tetraazamacrocyle. Concurrent density functional theory molecular modelling studies produced an energetic rationale for the unexpected [Zn(OAc)(H2 O)] + coordination motif present in all of the Zn 2+ cross‐bridged tetraazamacrocycle crystal structures, which differs from the chelating acetate [Zn(OAc)] + structures of known unbridged and side‐bridged tetraazamacrocyclic Zn 2+ ‐containing CXCR4 antagonists. Abstract : Have you got your complexes crossed? Complexes of cross‐bridged tetraazamacrocycles exhibit Cu 2+ bound to acetate in a monodentate fashion yielding square‐pyramidal geometries with the acetate occupying an equatorial position (base of the pyramid) and having a relatively short Cu−O bond (ca. 1.95 Å), which may explain the strong binding of Cu 2+ cross‐bridged bis‐cyclam CXCR4 antagonists. The Zn 2+ complexes all locate acetate equatorially, hydrogen bonded to a cis water molecule to form distorted octahedral coordination geometries.